Correlation between visceral abdominal fat with body mass index in type 2 diabetic patient using DEXA scan - Hairudduin, Nor Fazliza (2017)
Objective: To correlate between visceral abdominal fat with body mass index (BMI) in patients with type 2 diabetis mellitus using dual – energy X-ray absorptiometry (DEXA) scan. Methodology: Patients (n=29) were recruited from Klinik Pakar, Hospital USM, Kelantan. The inclusion criteria included type 2 diabetic patient with age ranging from 20 to 79 years. Ptients who were pregnant, weighed more than 240kg and had a height of more than 190 were excluded from the study. DEXA scan was performed to quantify the visceral abdominal fat. Results: There was significant correlation between visceral abdominal fat with BMI in type 2 diabetic patients (r=0.68, p=0.000). There was also significant correlation between visceral abdominal fat with BMI according to gender (Malay: r=0.74, p=<0.001; Chinese: r=0.78, p=0.007) and race ( Male: r= 0.616, p=0.043; Female: r= 0.68, p=0.002). Conclusion: BMI and DEXA scan can be used as a tool for screening of visceral abdominal fat in patients with type 2 diabetis mellitus.